Clear Cell Adenocarcinoma Arising from Endometriosis in the Groin: Wide Resection and Reconstruction with a Fascia Lata Tensor Muscle Skin Flap - Shozo Yoshida; Akira Onogi; Masamitsu Kuwahara; Tomoko Uchiyama; Hiroshi Kobayashi (Hindawi Limited, 2018)
We herein report a case of clear cell carcinoma arising from endometriosis in the groin in a 53-year-old woman. The findings of MRI and FDG/PET-CT indicated a malignant tumor, and surgical biopsy confirmed adenocarcinoma of the female genital tract. The tumor including a part of the abdominal rectus muscle and rectus sheath, subcutaneous fat, skin, and the right inguinal ligament was resected en bloc. The defect in the abdominal wall was reconstructed with a fascia lata tensor muscle skin flap. The tumor was composed of clear cell adenocarcinoma arising from extrapelvic endometriosis. The patient received chemotherapy with gemcitabine and carboplatin for 6 cycles and had no evidence of recurrence 7 months after the treatment. We herein described the diagnosis and surgical management of endometriosis-associated carcinoma in the groin.